584. Investigation of the Association Between Neurocognitive Function and Depression in HIV Infection. (26th November 2018) - Mumford, Brigid; Pirrone, Vanessa; O'Hayer, C Virginia; Dampier, William; Wigdahl, Brian; O'Loughlin, Caitlin; Amat, Maelys; Szep, Zsofia
Abstract: Background: In the era of antiretroviral therapy, HIV-infected patients are living longer generating life expectancies similar to HIV uninfected individuals. Depression has been described as the most common neuropsychiatric complication among people living with HIV. Our primary aim was to examine any association between neurocognitive function and depression among individuals with HIV infection. Our secondary aim was to investigate any association between heightened inflammation and neurocognitive function and depression in HIV infection. Methods: We performed a cross-sectional study among patients living with HIV who receive care at the Drexel University Partnership Comprehensive Care Practice and who participate in the Drexel Medicine CNS AIDS Research and Eradication Study (CARES) Cohort Study. We included individuals who underwent a comprehensive neurocognitive assessment between September 1, 2013 and June 1, 2015. Chart reviews were conducted for all eligible participants to elicit diagnosis of depression based on ICD10 codes, presence of antidepressant medication and for engagement in psychiatric care Subject characteristics were described overall and by depression status. Categorical variables were evaluated using Fisher's exact tests and continuous variables were described using Mann–Whitney U tests. Results: One hundred ninety-seven participants with available neurocognitive evaluation were included, 64% male, mean age of 53 ± 7.8 and 88% African American. Overall 23% of patients had a diagnosis of depression based on medication, diagnosis code, and engagement in psychiatric care. We did not find an association between eurocognitive score and diagnosis of depression. Among individuals with available lab values for interleukin (IL)-6 and C-reactive protein (CRP) we did not find an association between level of inflammation and depression. Conclusion: As individuals with HIV are living longer, we are seeing a higher prevalence of comorbidities such as depression, but it is not clear what role HIV itself plays in comparison to traditional risk factors, and this needs further evaluation. In our study we did not find an association between neurocognitive impairment and depression in people living with HIV infection. Disclosures: All authors: No reported disclosures.